2021
DOI: 10.1186/s40104-021-00560-8
|View full text |Cite
|
Sign up to set email alerts
|

Feeding a Saccharomyces cerevisiae fermentation product improves udder health and immune response to a Streptococcus uberis mastitis challenge in mid-lactation dairy cows

Abstract: Background We aimed to characterize the protective effects and the molecular mechanisms of action of a Saccharomyces cerevisiae fermentation product (NTK) in response to a mastitis challenge. Eighteen mid-lactation multiparous Holstein cows (n = 9/group) were fed the control diet (CON) or CON supplemented with 19 g/d NTK for 45 d (phase 1, P1) and then infected in the right rear quarter with 2500 CFU of Streptococcus uberis (phase 2, P2). After 36-h, mammary gland and liver biopsies were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…A rich body of evidence suggests that SCFP supplementation is one such strategy. It has been demonstrated that SCFP stabilize the rumen microbial community (Tun et al, 2020), tend to reduce ruminal free LPS concentration, and enhance immune responses within and outside of the gut (Jensen et al, 2008;Perdomo Lozada, 2011;Li et al, 2012;Vailati-Riboni et al, 2021). As a result, we hypothesized that gut disruptions and inflammation during SARA can be attenuated by SCFP supplementation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A rich body of evidence suggests that SCFP supplementation is one such strategy. It has been demonstrated that SCFP stabilize the rumen microbial community (Tun et al, 2020), tend to reduce ruminal free LPS concentration, and enhance immune responses within and outside of the gut (Jensen et al, 2008;Perdomo Lozada, 2011;Li et al, 2012;Vailati-Riboni et al, 2021). As a result, we hypothesized that gut disruptions and inflammation during SARA can be attenuated by SCFP supplementation.…”
Section: Introductionmentioning
confidence: 97%
“…Examples of postbiotics used in dairy are Saccharomyces cerevisiae fermentation products (SCFP), which have been shown to benefit rumen fermentation (Zhu et al, 2017), milk production (Poppy et al, 2012), and efficiency of milk production of lactating dairy cows . Supplementation with SCFP also have been shown to reduce inflammation during pathogenic (Vailati-Riboni et al, 2021), physiological (Li et al, 2016), and immunological challenges (Jiang et al, 2018). It is proposed that functional metabolites, organic acids, vitamins, and antioxidants present in postbiotics, such as SCFP, may either be used as nutrients by members of gut microbiota or act as signaling molecules affecting microbe-microbe or microbe-host interactions and the physiological and immunological responses of the host (Salminen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The SCC in the present study was reduced by feeding S. cerevisiae ( p < 0.05). Similarly, some studies reported that yeast product supplementation improved the mammary gland health in lactating dairy cows and reduced the incidence of mastitis [ 4 , 7 ]. These results are not fully explained but may be due to immunomodulation with antioxidant and anti-inflammatory effects of yeast product supplementation [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, feed additives, including yeast supplements such as Saccharomyces cerevisiae, are widely used to improve the lactation performance and health in dairy cows [4,5]. Many studies have reported that feeding Saccharomyces cerevisiae positively influences the dry matter intake (DMI), rumen pH, nutrient digestibility, immune function and milk quality of dairy cows [5][6][7]. Because of its effects on the rumen fermentation and nutrient digestion, some authors have suggested that feeding yeast products may be most beneficial to dairy cows under heat stress [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for reduced SCC in SCFP-fed cows are not fully understood but likely involve the immunomodulatory effects of SCFP and the basal levels of immune activation (systemic and intramammary; as reviewed by Volman et al, 2008;Broadway et al, 2015). From a Streptococcus uberis challenge study, Vailati-Riboni et al (2019) observed that SCFP-fed cows recovered faster from the challenge with greater milk yield with reduced SCC. Further investigating the effect of dietary SCFP on mammary health is of interest.…”
mentioning
confidence: 99%